Influence of temperature on gas nitriding of Fe-Ni-Cu-Mo-C sintered alloys. (1st January 2000) - Molinari, A.; Straffelini, G.
In order to increase the mechanical properties of the diffusion layer of the nitrided Fe-Ni-Cu-Mo-C sintered alloy, the nitriding temperature was varied over a wide range, and some experiments at a temperature higher than that of the eutectoid reaction in the Fe-C-N system were carried out. In order to control the diffusion depth and, in turn, the dimensional variations, different pre-treatments for the closure of the interconnected pores were investigated. The microhardness profiles of the diffusion layers obtained at different temperatures were compared and interpreted on the basis of the microstructural transformations occurring during nitrogen diffusion. The results show that high temperature nitriding can really improve the mechanical properties of the treated material.